Potential cellular targets of platinum in the freshwater microalgae Chlamydomonas reinhardtii and Nitzschia palea revealed by transcriptomics - O. Hourtané; P. Gonzalez; A. Feurtet-Mazel; E. Kochoni; C. Fortin (Ecotoxicology, 2024)

Hierarchical phylogenetic community assembly of soil protists in a temperate agricultural field - Julien Roy; Florent Mazel; Kenneth Dumack; Michael Bonkowski; Matthias C. Rillig (Environmental Microbiology, 2022)
Protists are abundant, diverse and perform essential functions in soils. Protistan community structure and its change across time or space are traditionally studied at the species level but the relative importance of the processes shaping these patterns depends on the taxon phylogenetic resolution. Using 18S rDNA amplicon data of the Cercozoa, a group of dominant soil protists, from an agricultural field in western Germany, we observed a turnover of relatively closely related taxa (from sequence variants to genus‐level clades) across soil depth; while across soil habitats (rhizosphere, bulk soil, drilosphere), we observed turnover of relatively distantly related taxa, confirming Paracercomonadidae as a rhizosphere‐associated clade. We extended our approach to show that closely related Cercozoa encounter divergent arbuscular mycorrhizal (AM) fungi across soil depth and that distantly related Cercozoa encounter closely related AM fungi across soil compartments. This study suggests that soil Cercozoa community assembly at the field scale is driven by niche‐based processes shaped by evolutionary legacy of adaptation to conditions primarily related to the soil compartment, followed by the soil layer, giving a deeper understanding on the selection pressures that shaped their evolution.

Fluorescent epibiotic microbial community on the carapace of a Bahamian ostracod - J. Jarett; C. Fiore; C. Mazel; M. Lesser (Archives of Microbiology, 2013)

Impacts of Cd and Zn on the Development of Periphytic Diatom Communities in Artificial Streams Located Along a River Pollution Gradient - C. Gold; A. Feurtet-Mazel; M. Coste; A. Boudou (Archives of Environmental Contamination and Toxicology, 2003)

Optical spectra and pigmentation of Caribbean reef corals and macroalgae - M. R. Myers; J. T. Hardy; C. H. Mazel; P. Dustan (Coral Reefs, 1999)